Effect Of Return on Equity, Debt to Equity Ratio, and Current Ratio on Stock Return: Case Study of Industrial Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2022 Period - Rosdiana, Riska; Maya, Siska; Hermala, Irvan; Fathihani (CV ODIS, 2024)
This study analyzes the effect of Return on Equity, debt-to-equity ratio, and Current Ratio on Stock Return. The population in this study is industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period, with the sample used being as many as 13 companies. The sampling method used purposive sampling. The data collection method uses the documentation method, using stock prices, net income, equity, total debt, current assets, and current liabilities obtained through the websites finance.yahoo.com and idx.co.id. The data analysis method uses the panel data regression analysis method with the help of Eviews 9 software. The results of this study indicate that return on equity has a positive effect on stock returns. In contrast, the debt-to-equity and current ratios do not impact stock returns.